Parlamentní projev F. Udržala 28. listopadu 1934 - Charbuský, Miloš (Univerzita Pardubice, 2001)
František Udržal, a politician of the Agrarian Party was a Prime Minister of the Czechoslovak Republic in 1929 - 1932. After he was forced to resign, who considerably restricted his political activities. He delivered his essential parliamentary speech as lates as in the 28th November 1934. He explained in if in detail his views on national and international politic situation.
Keywords: Udržal, František; agrární strana; politika; Československo; 1934